Evaluation of investment funds through different performance measures - Borges Júnior, Dermeval Martins (2021)
Purpose - The aim of this study is to examine the evaluation of Brazilian equity funds from different performance measures.Theoretical framework - In the literature, several indexes are available that can be used to evaluate the performance of investment funds.Design/methodology/approach - Monthly return data were collected from 1,901 Brazilian equity funds. Fund performance was estimated using four indexes: the Sharpe ratio, the Sortino ratio, Jensen’s alpha, and the Treynor ratio.Findings - The results showed that all four performance measures are positively associated. This means that there are no significant differences in the ranking of Brazilian equity funds in terms of performance.Research, Practical & Social implications - The comparison of different performance indexes contributes to the literature on the subject by providing further data for researchers to adequately define the indexes considered in studies on the performance of funds.Originality/value - This study fills a gap in the literature regarding the analysis of performance measures of investment funds.Keywords - Mutual funds. Equity funds. Performance.